EFFECT OF CORPUS LUTEUM AND STATUS OF ANIMAL ON RECOVERY RATE OF OOCYTES IN OVINE - SOFI, K A; KHAN, M Z; lslam, R; LONE, F A (The Indian Journal of Animal Reproduction, 2010)
Genital organs of slaughtered ewes were collected from abattoirs in Srinagar city and transportedto the laboratory in warm normal saline solution containing 50μg gentamicin sulphate per ml. Uponarrival to the laboratory; the status of the reproductive tract (gravid or non-gravid) and ovaries for corpusluteum {with or without} were observed and recorded. The oocytes were collected separately fromovaries of gravid and non-gravid uteri as well as from ovaries with or without corpus luteum (CL) usingslicing method and graded as good, fair and poor for each ovary under stereo-zoom microscope. Thegood quality, usable and total oocytes harvested from ovaries without CL were significantly (p 0.05) higher for ovaries ofnon-gravid uteri (3.14, 4.92 and 6.45) than for ovaries of gravid uterus (1.96, 3.38 and 5.04 ). In conclusion,ovaries without CL were better for oocyte collection from abattoir ovaries in ovine.
Keywords: Recovery rate; Cqrpus Juteum; Pregnancy status; Ovlne